ANALISIS AGRONOMI DAN EKONOMI PAKET TEKNOLOGI BUJAKA (BUDIDAYA JAGUNG TOLERAN KEKERINGAN) DI KABUPATEN GORONTALO - Jaka Sumarno; Teddy Wahyana Saleh; Muhammad Fitrah Irawan Hannan; Hasyim Jamalu Moko; Aryandi Kurnia Rahman (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
Agronomic and Economic Analysis of BUJAKA Technology Package (Drought Tolerant Maize Cultivation Technology) in Gorontalo Regency. Drought stress has caused plant growth and yields to decrease. For this reason, it is necessary to assembly  a drought tolerant maize cultivation technology package. This study aims to analyze the growth, yield, and economic performance of the application of drought tolerant maize cultivation technology package (BUJAKA). The research was carried out for two planting seasons, namely 2019 and 2020 in Gorontalo District, Gorontalo Province. To determine the agronomic performance (growth and yield) of the application of the BUJAKA, a randomized block design (RBD) method was used as a treatment using 10 hybrid and composite maize varieties. In planting season I, the treatment was repeated 6 replications and planting season II was repeated 4 replications. To find out the economic performance, a farming analysis was carried out including revenue, costs, benefits and financial feasibility with a parcial budget analysis. The results showed that the BUJAKA technology package was able to increase the productivity of maize compared to the existing technology. The productivity of maize increased from 356,.01 kg / ha to 5215,95 kg / ha. Changing the application from existing technology to BUJAKA technology requires an additional fee of 39%, however, with an increase in productivity, the benefits obtained also increased by 4.63. 772 IDR/ ha (an increase of 50%). BUJAKA technology was financially feasible to be promoted to replace existing technology because the value of R> 1 (2,36).Keywords: agronomic performance, economy, maize technology, drought tolerant ABSTRAK Cekaman kekeringan menyebabkan pertumbuhan tanaman dan hasil  jagung menjadi menurun. Untuk itu perlu dilakukan perakitan paket teknologi budidaya jagung toleran cekaman kekeringan. Penelitian ini bertujuan untuk menganalisis keragaan pertumbuhan, hasil, dan ekonomi penerapan paket teknologi budidaya jagung toleran cekaman kekeringan (BUJAKA). Penelitian dilaksanakan selama dua musim tanam yaitu tahun 2019 dan 2020 di Kabupaten Gorontalo, Provinsi Gorontalo. Untuk mengetahui keragaan agronomi (pertumbuhan dan hasil) penerapan paket teknologi BUJAKA dilakukan metode Rancangan Acak Kelompok (RAK) sebagai perlakuan dengan menggunakan 10 varietas jagung hibrida dan komposit. Pada musim tanam I perlakuan diulang sebanyak 6 ulangan dan musim tanam II diulang sebanyak 4 ulangan. Untuk mengetahui keragaan ekonomi dilakukan analisis usahatani meliputi penerimaan, biaya, keuntungan dan kelayakan finansial dengan parcial budget analysis.  Hasil penelitian menunjukkan bahwa paket teknologi BUJAKA mampu meningkatkan produktivitas jagung dibandingkan teknologi eksisting. Produktivitas jagung meningkat dari 3567,01 kg/ha menjadi 5215,95 kg/ha. Perubahan penerapan dari teknologi eksisting menjadi teknologi BUJAKA, diperlukan tambahan biaya sebesar 39%, namun demikian, dengan peningkatan produktivitas maka keuntungan yang diperoleh juga meningkat sebesar Rp 4.635.772/ha (meningkat sebesar 50%). Teknologi BUJAKA layak secara finansial untuk dipromosikan menggantikan teknologi eksisting oleh karena nilai R >1 (2.36).Kata kunci: keragaan agronomi, ekonomi, teknologi jagung, toleran kekeringan